IMPLEMENTASI KODE ETIK GURU UNTUK MENINGKATKAN KINERJA GURU PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI - Maghfirah Insannia; Rahma Yanti; Wedra Aprison (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Teachers as role models have a very strategic position and role in all educational efforts. The position of teachers as professional educators functions to increase the dignity and role of teachers as learning agents in improving the quality of national education. In realizing professional work principles. Indonesian teachers, especially Islamic Religious Education (PAI) teachers, are required to have pedagogical, personality, social and professional competencies in accordance with developments in science and technology. Apart from that, teacher morality must always be maintained because dignity and nobility as the basic elements of teacher morality lie in the excellence of their behavior, reason and dedication. Education services will be better if the teacher code of ethics is applied consistently. The Indonesian Teacher Code of Ethics contains norms and principles that serve as guidelines for attitudes and behavior in carrying out professional duties as educators, community members and citizens with the aim of placing teaching as an honorable, noble and dignified profession that is protected by law. The research for writing this article used the literature study method. Literature study is the process of collecting data by collecting library data, namely library literature from books, articles and journals. In this research the author uses a critical descriptive approach by prioritizing analysis of data sources. The data source for this article comes from several articles or journals written by educational experts who have experience.